Cover Crop Impacts on Water Dynamics and Yields in Dryland Wheat Systems on the Colorado Plateau - Lisa Eash; Abdel F. Berrada; Kathleen Russell; Steven J. Fonte (Agronomy, 2021)
On the semiarid Colorado Plateau, dryland farmers are challenged by degraded soils and unreliable precipitation. While cover crops have been shown to support soil fertility, control erosion, and enhance soil water capture, they also use limited soil water and, thus, may impact cash crop productivity in dryland systems. Most literature on cover crops comes from relatively humid climates, where yield penalties due to cover crops may be less pronounced. Two field trials were conducted in Southwestern Colorado to assess the short-term viability of cover crops in dryland systems in this region. The effect of cover crops on subsequent winter wheat (Triticum aestivum L.) yield ranged from a decrease of 78% to an increase of 13%, depending on the amount of cover crop biomass produced in the previous year. Cover crop biomass was inversely correlated with soil nitrate levels and soil water storage at wheat planting, which decreased by 0.39 mg kg−1 and 10 mm, respectively, per 1000 kg ha−1 of cover crop biomass produced. Less available soil water and immobilized N therefore appeared to contribute to wheat yield reductions. These impacts are particularly important for semiarid environments, where decomposition of residue is water-limited and soil water recharge depends on unpredictable precipitation patterns.